2022
DOI: 10.3390/ijms23042109
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the ATP-Binding Cassette (ABC) Transporter Family in Zea mays L. and Its Response to Heavy Metal Stresses

Abstract: The ATP-binding cassette (ABC) transporter family is one of the largest eukaryotic protein families. Its members play roles in numerous metabolic processes in plants by releasing energy for substrate transport across membranes through hydrolysis of ATP. Maize belongs to the monocotyledonous plant family, Gramineae, and is one of the most important food crops in the world. We constructed a phylogenetic tree with individual ABC genes from maize, rice, sorghum, Arabidopsis, and poplar. This revealed eight familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Similarly, the molecular weight of the CcABC proteins ranged from 6.97 to 345.38. The isoelectric point of the CcABC proteins lies in the range of 4.44 to 10.74 in the same manner as it has been reported in the ABC proteins of plants like Zea mays (Guo et al, 2022), 5.08 to 9.74 strawberry (Shi et al, 2020), 5.4 to 8.96 in cotton (Sun N et al 2021), 4.41 to 10.5 in soyabean (Mishra et al 2019) 5.05 to 10.48 in peach (Sylvia et al 2023)and tomato (Ofori PA et al 2018). In C. cajan, out of 159 CcABC proteins, 105 proteins were basic and 50 were acidic in nature, whereas 2 were neutral proteins.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similarly, the molecular weight of the CcABC proteins ranged from 6.97 to 345.38. The isoelectric point of the CcABC proteins lies in the range of 4.44 to 10.74 in the same manner as it has been reported in the ABC proteins of plants like Zea mays (Guo et al, 2022), 5.08 to 9.74 strawberry (Shi et al, 2020), 5.4 to 8.96 in cotton (Sun N et al 2021), 4.41 to 10.5 in soyabean (Mishra et al 2019) 5.05 to 10.48 in peach (Sylvia et al 2023)and tomato (Ofori PA et al 2018). In C. cajan, out of 159 CcABC proteins, 105 proteins were basic and 50 were acidic in nature, whereas 2 were neutral proteins.…”
Section: Discussionsupporting
confidence: 74%
“…All the motifs of ABC gene family were highly conserved as reported in peach (Sylvia C et al, 2023), brassica rapa (Yan C et al2017), zea mays (Guo Z et al 2022), soyabean (Huang J et al 2021) and capsicum (Ortiz C et al 2019). It were also mentioned in the pineapple (Chen P et al 2017), hexaploid wheat (Bhati KK et al 2015), barley (Zhang Z et al 2020), strawberry (M. Shi et al, 2020), and flax (Khan et al2020) that all the conserved motifs were identified.…”
Section: Discussionmentioning
confidence: 72%
“…Families of Serine/Threonine protein kinases (SNRK-2) are known to enhance cold stress tolerance in Arabidopsis 88 . In addition, enhanced expression of few of SNRK-2 genes have also been reported under cold stress in maize 89,90 . Further, WRKY transcription factors constitute one of the largest transcription factor families in plants and play important role in plant growth and thermal stress response 91 .…”
Section: Discussionmentioning
confidence: 89%
“…ABC transporters can transport multiple types of substrates across the plasma membrane via ATP hydrolysis in response to environmental stress [ 56 , 57 ]. A previous study in M. domestica demonstrated that MdABCF in pollen could combine with S-RNase, a key protein of GSI, and transport it to the cytoplasm of the pollen tube to facilitate its cellular cytotoxic function [ 34 ].…”
Section: Discussionmentioning
confidence: 99%